2010
DOI: 10.5137/1019-5149.jtn.3857-10.0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term benefit of bilateral subthalamic deep brain stimulation on camptocormia in parkinson’s disease

Abstract: We report the case of a 63-year-old female with a long history of severe Parkinson's disease (PD) and subsequent onset of debilitating camptocormia who underwent successful bilateral subthalamic nucleus deep brain stimulation surgery (STN DBS). The literature and previous reports are reviewed. The patient history and details of the surgical procedure are reported including the implantable pulse generator (IPG) settings and response to stimulation. The results of her PD symptom and camptocormia improvements are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…These three studies report comparisons of pre‐ and postsurgical means, but individual patient data are not available . Of the remaining 35 articles, there were three additional retrospective cohort studies, 12 case series with sample sizes of up to 25 patients, and 20 case reports …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These three studies report comparisons of pre‐ and postsurgical means, but individual patient data are not available . Of the remaining 35 articles, there were three additional retrospective cohort studies, 12 case series with sample sizes of up to 25 patients, and 20 case reports …”
Section: Resultsmentioning
confidence: 99%
“…Outcome measures were also variable. Most articles reported postural abnormalities as qualitative clinical observations . Some of them provided figure(s) and/or video(s) allowing for a semiquantitative estimation of the corresponding postural angles .…”
Section: Resultsmentioning
confidence: 99%
“…Although no such cases were included in our study, we cannot deny that this exceptional type of camptocormia contradicts our hypothesis that postoperative camptocormia improvement parallels its levodopa responsiveness. Lyons et al 30 reported a patient with PD with levodopa-unresponsive camptocormia that showed prolonged improvement after STN stimulation. Their patient's preoperative daily antiparkinsonian medication (500/125 mg levodopa/carbidopa, 4 mg pergolide and 200 mg amantadine) was reduced to only 100/25 mg of levodopa/carbidopa 5 years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…857 Third, there have been a few cases showing that camptocormic symptoms could be reversed following levodopa. 6369 Fourth, camptocormic symptoms were also improved by high-frequency subthalamic nucleus 197075 or globus pallidus interna deep brain stimulation 7677 (STN or GPi-DBS) together with improved motor symptoms in patients with PD. The argument against this idea is that most cases of camptocormia in PD did not respond to either levodopa 858 or DBS.…”
Section: Pathogenesis Of Camptocormia In Pdmentioning
confidence: 99%
“…The time of last follow-up ranged from 6 to 60 months after surgery. In PD with camptocormia, STN-DBS 101958707578102 and GPi-DBS 197678 have both been used. The details of studies of DBS in PD with camptocormia are summarised in table 3.…”
Section: Treatment Modalities For Camptocormiamentioning
confidence: 99%